(untitled) (Biological Sciences - PJSIR, 1995)
ESSENTIAL OILS OF THE FAMILY GRAMINEAE WITH ANTIBACTERIAL ACTIVITY Part 2. The Antibacterial Activity Of A Local Variety Of Cymbopogan Citratus Oil And Its Dependence On The Duration Of Storage